Automatic Mirror Folding Design Arduino-Based - Mira Esculenta Martawati; Sugeng Hadi Susilo; Asrori A; Lulut W (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Abstract. The rear-view mirror is one of the main devices found in cars. A mirror is a mirror used to see the traffic of a vehicle behind when it is about to veer, stop or change lanes. The purpose of this study was to design a pre-crash performance test of the rearview mirror. That is a system that will automatically perform mirror folding automatically based on the distance of the object in front of it. The system will reduce the risk of broken or scratched due to driver negligence. The research method at a time when the barrier is 30cm (±20cm) away from the front or back of the rearview mirror will read that distance which will then transmit to the Arduino. Arduino will process the data and send data for the speed reduction process by warning that there is an object in front or behind the rearview mirror and when the distance is <30cm from the barrier object, then the Arduino will order to fold the rearview mirror automatically, by activating the servo motor to fold the rear and rearview mirrors. The result of this study was to find out the performance of the GP2Y0A21 distance sensor reading and the performance of the rearview mirror pre-crash system. In this study, the bound variable was the distance measurement of the sensor's reading. The free variable used is the sensor reading metering distance displayed on the LCD (Liquid Crystal Display).